Stanley Crouch, Kansas City Lightning: The Rise and Times of Charlie Parker - Scott, Andrew (Jazz Research Journal, 2023)
Stanley Crouch, Kansas City Lightning: The Rise and Times of Charlie Parker. New York: HarperCollins, 2013. 384 pp. ISBN 978-0-06-200559-5 (hbk). $37.86.